The lesser gods of the Sahara : social change and contested terrain amongst the Tuareg of Algeria - Keenan, Jeremy, 1945- (London ; Portland, OR : Frank Cass, 2004)
The eight essays that comprise this collection cover various aspects of social change and contested terrain amongst the Tuareg people Algeria.
Introduction : indigenous rights and a future politic -- Amongst Algeria's Tuareg after forty years of independence -- From tit (1902) to tahilahi (2002) : a reconsideration of the impact of and resistance to French pacification and colonial rule by the Tuareg of Algeria (the northern Tuareg) -- Ethnicity, regionalism, and political stability in Algeria's Grand Sud -- Dressing for the occasion : changes in the symbolic meanings of the Tuareg veil -- The end of the matriline? : the changing roles of women and descent amongst the Algerian Tuareg -- The last nomads : nomadism among the Tuareg of Ahaggar (Algerian Sahara) -- The lesser gods of the Sahara -- Contested terrain : tourism, environment, and security in Algeria's extreme south.
Includes bibliographical references (pages 266-273) and index.
Print version record.
Appendices in French.
eBooks on EBSCOhost
Keywords: Tuaregs -- History; Tuaregs -- Ethnic identity; Tuaregs -- Social life and customs; Social change -- Algeria; Cultural property -- Protection -- Algeria; Algeria -- Colonization; Algeria -- Race relations; Algeria -- Politics and government; Touaregs -- Histoire; Touaregs -- Identité ethnique; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Colonization; Cultural property -- Protection; Politics and government; Race relations; Social change; Tuaregs; Tuaregs -- Ethnic identity; Tuaregs -- Social life and customs; Algeria; Electronic books; History